From Congenital Disorders of Fat Malabsorption to Understanding Intra-Enterocyte Mechanisms Behind Chylomicron Assembly and Secretion - Levy, Emile; Beaulieu, Jean François; Spahis, Schohraya (Frontiers in Physiology, 2021)
During the last two decades, a large body of information on the events responsible for intestinal fat digestion and absorption has been accumulated. In particular, many groups have extensively focused on the absorptive phase in order to highlight the critical ‘’players’’ and the main mechanisms orchestrating the assembly and secretion of chylomicrons (CM) as essential vehicles of alimentary lipids. The major aim of this article is to review understanding derived from basic science and clinical conditions associated with impaired packaging and export of CM. We have particularly insisted on inborn metabolic pathways in humans as well as on genetically modified animal models (recapitulating pathological features). The ultimate goal of this approach is that ‘’experiments of nature’’ and in vivo model strategy collectively allow gaining novel mechanistic insight and filling the gap between the underlying genetic defect and the apparent clinical phenotype. Thus, uncovering the cause of disease contributes not only to understanding normal physiologic pathway, but also to capturing disorder onset, progression, treatment and prognosis.